The neuroprotective effects of bilingualism upon the inferior parietal lobule: A Structural Neuroimaging Study in Aging Chinese Bilinguals - Abutalebi, Jubin; Canini, Matteo; Della Rosa, Pasquale A.; Green, David W.; Weekes, Brendan S. (Journal of neurolinguistics, 2015)
It is a timely issue to understand the impact of bilingualism upon brain structure in healthy aging and upon cognitive decline given evidence of its neuroprotective effects. Plastic changes induced by bilingualism were reported in young adults in the left inferior parietal lobule (LIPL) and its right counterpart (RIPL) (Mechelli et al., 2004). Moreover, both age of second language (L2) acquisition and L2 proficiency correlated with increased grey matter (GM) in the LIPL/RIPL. However it is unknown whether such findings replicate in older bilinguals. We examined this question in an aging bilingual population from Hong Kong. Results from our Voxel Based Morphometry study show that elderly bilinguals relative to a matched monolingual control group also have increased GM volumes in the inferior parietal lobules underlining the neuroprotective effect of bilingualism. However, unlike younger adults, age of L2 acquisition did not predict GM volumes. Instead, LIPL and RIPL appear differentially sensitive to the effects of L2 proficiency and L2 exposure with LIPL more sensitive to the former and RIPL more sensitive to the latter. Our data also intimate that such differences may be more prominent for speakers of languages that are linguistically closer such as in Cantonese-Mandarin bilinguals as compared to Cantonese-English bilinguals. •Elderly bilinguals have increased GM volumes in the inferior parietal lobules (IPL) than monolinguals.•Unlike younger adults, age of L2 acquisition does not predict GM volumes.•The IPL appears differentially sensitive to the effects of L2 proficiency and L2 exposure.•Differences are more prominent for speakers of linguistically closer languages than distant languages.